Upaya Tim Public Relations dalam Meningkatkan Citra dan Kepercayaan Khalayak Terhadap SMA Al-Kamal - Farhana, Selma; Ummanah, Ummanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to explain the steps or efforts of the public relations team from SMA Al-Kamal in increasing interest in learning, image and public trust in the school. Given the condition of the school which has been facing land disputes for quite a long time. This study used the case study method with observation and interview data collection techniques. The results of the research show that there are several efforts that have been made by schools through the public relations team, these efforts are by using word of mouth techniques and providing additional or extracurricular activities at school. These two efforts have had a positive impact on increasing student interest in learning, the quantity of prospective new students and public enthusiasm for enrolling their children at Al-Kamal High School. In conclusion, the public relations team at Al-Kamal High School implemented several efforts to increase student learning interest, image and audience trust in Al-Kamal High School, these efforts included the application of word of mouth and the provision of extracurricular activities at school. Keywords: Effort, Public Relations, Image, Audience Trust, Al-Kamal High School